HUBUNGAN MINAT DAN HASIL BELAJAR MATERI ATLETIK NOMOR LARI MAHASISWA 2013 JURUSAN PENKEPOR FIK UNESA (Arena, 2013)
Abstract: The purpose of this research was to correlations between enthusiasm toward Atletic, and achievement in Atletic. The population of the study was the training students of Penkep.Or FIK UNESA. There were 140 subjects sample chosen from the population. The Pearsonâs Product Moment and Multiple Correlation were applied to analyze the data. The results showed that: there was correlation between achievement in Atletic there was correlation between enthusiasm toward Atletic; achievement in Atletic can be predicted from enthusiasm toward Atletic. Keywords: prestasi belajar mahasiswa, minat, Atletik